PENGEMBANGAN BAHAN AJAR INTERAKTIF TUTORIAL DALAM PEMBELAJARAN MATEMATIKA SISWA SMP - Isna Rafianti; Yani Setiani; Indhira Asih Vivi Yandari (Universitas Sultan Ageng Tirtayasa, 2018)
This research is motivated by rapid technological developments. More and more effort needs to be done in the utilization of technology results in learning. Teachers are expected to be able to use the tools provided from the school and not be covered by tools that are compatible with the development and turn of the times. Besides being able to use the tools available, teachers can also be used to create media that will be used as an available medium. One of the media used is interactive, in addition to junior high school students using tutorials to make it easier to use. The purpose of this research is to develop interactive learning in junior high school mathematics. The research was conducted in accordance with the research and development procedures consisting of: 1) preliminary study, 2) research planning, 3) development design, 4) preliminary field testing, 5) initial reference trial. In the preliminary stage of the field test, interactive teaching materials was validated by mathematicians, educational experts and multimedia specialists to assess the validity level of the product, which states that it is highly valid. In addition, limited tests were conducted on nine students to see the feasibility response that the results declared feasible, meaning interactive teaching materials learning math tutorial interesting to learn or use. Keywords: Interactive Teaching Materials, Tutorials